1988
DOI: 10.1288/00005537-198806000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Tracheobronchial foreign bodies

Abstract: A retrospective review of 88 cases of foreign body aspiration was undertaken. The patients ranged in age from 5 months to 73 years; the peak incidences of foreign body aspiration occurred in children less than 3 years of age and in adults older than 50 years. Sixty-one of the 88 patients were male. Physical examination was abnormal in 61% of patients. The most common radiographic abnormality was inspiratory-expiratory abnormality, seen in 27% of patients. Rigid endoscopy under general anesthesia was the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
101
1
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 11 publications
13
101
1
10
Order By: Relevance
“…McGuirt et al [8] has also observed male:female ratio of 2:1 stating the reason for this male predominance as more adventurous nature of males.…”
Section: Discussionmentioning
confidence: 92%
“…McGuirt et al [8] has also observed male:female ratio of 2:1 stating the reason for this male predominance as more adventurous nature of males.…”
Section: Discussionmentioning
confidence: 92%
“…If there is a suspicion for multiple diminutive FBs or fragments, we recommend performing a flexible bronchoscopy after FB abstraction, to evaluate the entire tracheobronchial tree (31,58).…”
Section: Mediastinal Shiftmentioning
confidence: 99%
“…Specifically, for this reason, FBA should be considered in all children with atypical or prolonged pulmonary symptoms. The delay in diagnoses can lead to a spectrum of complications ranging from life-threatening airway obstruction, to chronic wheezing, recurrent pneumonia, or failure to thrive [17,27,34,35]. The nationwide survey conducted in Japan revealed that diagnoses of inhaled FB were delayed by more than 24 hours in approximately half of the patients.…”
Section: Discussionmentioning
confidence: 99%